The effects of hydration and carbohydrate supplementation during exposure to moderate altitude
Adaptation to altitude while training presents a number of problems and unusual demands for swimmers. Altitude exposure results in an increased need for fluids. When fluid hydration and carbohydrate supplementation were provided, swimmers had an easier time adjusting, were not bothered by altitude sickness or fatigue, and displayed a positive shift in plasma volume. The ability to complete workouts early in the exposure was slightly improved and repeat times were closer to sea-level times. These desirable factors were not evident in a group that did not increase fluid or carbohydrate intake. After two weeks of training all swimmers showed declines in serum ferritin values. This indicated a loss of iron storage which is required for oxygen transportation. This response, although not immediate, may be a slower adaptive response that needs to be monitored. It justifies the recommendation for iron supplementation prior to and for the whole time at altitude. Implication: Carbohydrate fortified drinks and iron are important dietary supplements which facilitate altitude adaptation. The ingestion of these should be standard procedures when attempting to make this training change.